Radiation biology of medical imaging - Kelsey, Charles A.; Heintz, Philip; Sandoval, Daniel; Chambers, Gregory D. (Gregory Daniel); Adolphi, Natalie; Paffett, Kimberly (Hoboken, New Jersey : Wiley Blackwell, 2013)
This book provides a thorough yet concise introduction to quantitative radiobiology and radiation physics, particularly the practical and medical application. Beginning with a discussion of the basic science of radiobiology, the book explains the fast processes that initiate damage in irradiated tissue and the kinetic patterns in which such damage is expressed at the cellular level. The final section is presented in a highly practical handbook style and offers application-based discussions in radiation oncology, fractionated radiotherapy, and protracted radiation among others. The text is also supplemented by a Web site.
Anatomy and physiology -- The cell -- Radiation characteristics and units -- Radiation interactions with tissue.
Includes bibliographical references.
Print version record and CIP data provided by publisher.
Keywords: Radiobiology; Diagnostic imaging; Radiobiology; Diagnostic Imaging; Tissues -- radiation effects; Medical; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Diagnostic imaging; Radiobiology; Electronic books